Perlindungan Hak Nafkah Anak dari Perkawinan Siri: Kajian Itsbat Nikah Dalam Perspektif Hukum Islam Dan Keadilan - Warisni, Rinrin; Heniarti, Dini Dewi; Nurhasanah, Neneng (Tasyri' : Journal of Islamic Law, 2025)
The increasing prevalence of unregistered (siri) marriages in Indonesia has raised serious social concerns and legal challenges, particularly regarding the protection of children's rights. Children born from siri marriages are often deprived of their legal entitlements, especially the right to financial support (nafaqah), due to the absence of official marriage registration that provides legal certainty. This study aims to analyze the role of itsbat nikah (marriage validation) as a legal mechanism to guarantee the child’s right to maintenance in the context of siri marriages. Using a normative juridical approach and library research method, the study draws from national regulations—such as Law No. 1 of 1974 and the Compilation of Islamic Law (KHI)—as well as Islamic legal doctrines and the framework of maqāṣid al-sharī‘ah. The findings reveal that the lack of legal documentation places children in a vulnerable and discriminatory position, especially in accessing their rights. Marriage registration is a crucial step toward ensuring justice and legal protection for children. Within the Islamic legal perspective, safeguarding children's welfare aligns with the objective of preserving lineage (ḥifẓ al-nasl) and promoting family well-being. Itsbat nikah services are thus viewed as a strategic state policy that addresses the legal gaps arising from unregistered marriages. This study recommends strengthening the accessibility, affordability, and efficiency of itsbat nikah procedures as a tangible form of state responsibility in securing justice for children and upholding the protective function of the law.